In‐Well Degassing of Monitoring Wells Completed in Gas‐Charged Aquifers. Issue 1 (22nd August 2022) - Morais, Tiago A.; Ryan, M. Cathryn
Abstract: Total dissolved gas pressure ( P TDG ) measurements are useful to measure accurate in situ dissolved gas concentrations in groundwater, but challenged by in‐well degassing. Although in‐well degassing has been widely observed, its cause(s) are not clear. We investigated the mechanism(s) by which gas‐charged groundwater in a recently pumped well becomes degassed. Vertical P TDG and dissolved gas concentration profiles were monitored in the standing water column (SWC) of a groundwater well screened in a gas‐charged aquifer for 7 days before and 15 days after pumping. Prior to pumping, P TDG values remained relatively constant and below calculated bubbling pressure ( P BUB ) at all depths. In contrast, significant increases in P TDG were observed at all depths after pumping was initiated, as fresh groundwater with elevated in situ P TDG values was pumped through the well screen. After pumping ceased, P TDG values decreased to below P BUB at all depths over the 15‐day post‐pumping period, indicating well degassing was active over this time frame. Vertical profiles of estimated dissolved gas concentrations before and after pumping provided insight into the mechanism(s) by which in‐well degassing occurred in the SWC. During both monitoring periods, downward mixing of dominant atmospheric and/or tracer gases, and upwards mixing of dominant groundwater gases were observed in the SWC. The key mechanisms responsible for in‐well degassing were (i) bubble exsolution when P TDG exceeded P BUB as gas‐charged well water moves upwards in the SWC during recovery (i.e., hydraulic gradient driven convection), (ii) microadvection caused by the upward migration of bubbles under buoyancy, and (iii) long‐term, thermally driven vertical convection.